Stimulation of Children's Gross Motor Development through Gross Motor Skill Carpets - Sunarni, Neli; Litasari, Resna; Roslianti, Elis (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Introduction & Objective: Neonatal anemia is a common health problem, particularly in developing countries, and contributes to increased morbidity and mortality in infants. One effective intervention that can be implemented immediately after birth is delayed cord clamping, which involves delaying the clamping of the umbilical cord for 1–3 minutes to allow for blood transfusion from the placenta to the infant. This practice is associated with increased hemoglobin levels in newborns. Method: This study is a literature review analyzing seven selected research articles published between 2019 and 2024, from both national and international journals. Inclusion criteria included experimental or quasi-experimental studies evaluating the effects of delayed cord clamping on hemoglobin levels and newborns. Data were analyzed narratively and comparatively. Result: All analyzed studies showed that delayed umbilical cord clamping has a positive impact on increasing hemoglobin levels and the hematological status of newborns. Newborns who underwent delayed umbilical cord clamping had higher hemoglobin, hematocrit, and iron stores compared to those who had their umbilical cord clamped earlier. Some studies also noted improved blood pressure stability and organ perfusion, particularly in preterm infants. Conclusion: Delayed cord clamping is a simple, safe, and effective intervention that can increase hemoglobin levels and improve the hematological status of newborn infants. The routine implementation of delayed cord clamping should be considered in delivery protocols as a preventive measure against neonatal anemia.